Phylogeny and taxonomy of Himerometroidea (Echinodermata: Crinoidea) - Taylor, Kristian H.; Rouse, Greg W.; Messing, Charles G. (Zootaxa, 2023)
Himerometroidea is a clade of chiefly shallow-water, tropical, feather-star crinoids that is currently divided, based on morphology, into four families comprising 119 extant species in 31 genera. Our molecular phylogenetic results, based on three mitochondrial (CO1, 16S, CytB) and two nuclear (ITS and 28S) markers for 55 accepted species in 23 of the extant genera, allow for six clades within Himerometroidea to be given family ranks. Maximum parsimony, maximum likelihood, and Bayesian inference analyses recovered largely congruent topologies with varying nodal support. A new classification revises generic placements among five families: Himerometridae, Colobometridae, and Mariametridae, all retained, and Pontiometridae and Stephanometridae both resurrected. Zygometridae is no longer accepted, since the type genus of the family, Zygometra, falls within Himerometridae. Catoptometra was recovered as a sister clade with respect to those treated herein as a new family, Catoptometridae. Two genera, Iconometra and Analcidometra, are retained within Himerometroidea but without family assignments pending further assessment of their positions. Currently published diagnostic and descriptive morphological features are noted where possible to support taxonomic names in the recovered phylogeny, although more examination of morphology is needed to identify synapomorphies and designate taxon names formally.